Impact of Foreign Direct Investment on Economic Growth - Dhungel, Bashu Dev; Lamichhane, Pitamber (Humanities and Social Sciences Journal, 2023)
Foreign direct investment (FDI) is a force of economic growth. FDI fills the gap between demand for capital and supply of capital that rise the productive investment and economic growth within the country. This paper aims to investigate the impact of FDI on economic growth of the country. Engel-Granger cointegration test is used by employing the time series data of 1995/96—2021/22 and error correction model. Neo-classical growth model is the main basis single equation model whereas real FDI is explanatory variable and GDP is the proxy for economic growth. Cointegration results confirms FDI makes the positive impact on economic growth in short-run as well as in long-run. The error correction term (0.67) indicates the disequilibria of GDP move towards the equilibrium at the speed of 65% in successive year. Therefore, this paper concludes to raise the FDI flows within the country. The Government should make the favorable environment — control money supply, direct remittance towards productive sector—for foreign investors which leads to rise economic growth within the country.